2019
DOI: 10.22146/jp.49523
|View full text |Cite
|
Sign up to set email alerts
|

Survival Strategies of Indonesian Immigrants in Kota Kinabalu, Sabah, Malaysia

Abstract: Findings of studies on the presence of immigrant workers in Malaysia often present negative social and economic implications. Their entry into the country is frequently a contentious issue due to their presence associated often with illegal foreign workers. This paper however is an attempt to provide insights into the involvement of Indonesian immigrants in the food business sector, their business adaptability and their survival strategies in a foreign land. The Indonesian immigrants’ experiences, from their b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Sabah is the second largest oil palm producing state in Malaysia (after Sarawak), contributing about 25 percent of the country’s oil palm (Reuters Staff, 2020). The significance of focusing the oil palm production in Sabah also lies on the complex intersection between the sector and a range of social phenomenon such as migration, poverty, high level of remoteness, lack of national identity and legal employment status, predominantly among the Indonesian and Filipino workers and their children (World Vision, 2012; Abdul Aziz and Iskandar, 2017; Dzurizah and Jalihah, 2014). Sabah is unique, as opposed to Peninsular Malaysia, in that migrant workers are legally allowed to have their family members (spouses and children) to accompany them to stay in Sabah (Puder, 2019).…”
Section: Research Contextmentioning
confidence: 99%
“…Sabah is the second largest oil palm producing state in Malaysia (after Sarawak), contributing about 25 percent of the country’s oil palm (Reuters Staff, 2020). The significance of focusing the oil palm production in Sabah also lies on the complex intersection between the sector and a range of social phenomenon such as migration, poverty, high level of remoteness, lack of national identity and legal employment status, predominantly among the Indonesian and Filipino workers and their children (World Vision, 2012; Abdul Aziz and Iskandar, 2017; Dzurizah and Jalihah, 2014). Sabah is unique, as opposed to Peninsular Malaysia, in that migrant workers are legally allowed to have their family members (spouses and children) to accompany them to stay in Sabah (Puder, 2019).…”
Section: Research Contextmentioning
confidence: 99%
“…When female children are involved in agricultural activities, the type of work they do often differs from male children. For example, male children tend to use sharp tools and undertake chemical spraying (see Carter & Roelen, 2017), while female children usually undertake more lighter works such as collecting loose fruits (Dzurizah & Jalihah, 2014), and bringing meals and water to their parents (Carter & Roelen, 2017). Semi-structured interviews with several female respondents found that while some female children are expected to help parents undertake oil palm activities, they are also responsible for helping parents take care of their younger siblings at home and performing everyday household chores.…”
Section: Children's Involvement In Oil Palm Activitiesmentioning
confidence: 99%
“…In Sabah specifically, there has been a growing literature studying the employment of children and/or child labor. In Sabah specifically, these studies explained the intersection between child labor, household poverty and geographical remoteness (see Abdul Aziz & Iskandar, 2017; Dzurizah & Jalihah, 2014; Pye et al, 2012; World Vision, 2012); children working in long hours, less pay and barriers to education (see Ibrahim & Shah, 2014); and children affected by cross-border migration, irregularity, and lack of documentation (see Earthworm Foundation, 2019; Ibrahim & Shah, 2014; Ismail, 2008; Puder, 2019; Wahab & Dollah, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation